2019
DOI: 10.1186/s13104-019-4176-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of skin-to-skin contact (SSC) during the postpartum stay and its determinant factors among mothers at public health institutions in Ethiopia

Abstract: ObjectiveThe study aimed at assessing skin-to-skin contact (SSC) during the postpartum stay and its determinant factors among mothers at public health institutions in Ethiopia.ResultA total of 384 mothers-indexed newborns admitted in postnatal wards were interviewed. The prevalence of mothers’ SSC practice to their newborns with in the first 1 h during the postpartum stay was 28.1%. Mothers education (AOR = 18.23 [95% CI 5.26, 63.52]), and number of ANC visits (AOR = 8.55 [95% CI 1.05, 69.54]) were independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
4
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 17 publications
4
25
4
5
Order By: Relevance
“…The practice of KMC among mothers who gave birth in the health facilities was 1808 (62.1%), 95% CI (60,3, 63.9).The others 1102(37.9%), 95%CI(36.1, 39.7) of mothers did not practiced KMC while they were in health facilities, although they gave birth in a health facilities too. The current study's level of KMC practice is higher than studies that reported 41.9% KMC (26), 46.4% KMC, 54.15% KMC (27), and 28.1% KMC (28). The difference might be as a result of study population difference, sample size difference, eligibility criteria, and socio-demographic difference.…”
Section: Discussioncontrasting
confidence: 75%
“…The practice of KMC among mothers who gave birth in the health facilities was 1808 (62.1%), 95% CI (60,3, 63.9).The others 1102(37.9%), 95%CI(36.1, 39.7) of mothers did not practiced KMC while they were in health facilities, although they gave birth in a health facilities too. The current study's level of KMC practice is higher than studies that reported 41.9% KMC (26), 46.4% KMC, 54.15% KMC (27), and 28.1% KMC (28). The difference might be as a result of study population difference, sample size difference, eligibility criteria, and socio-demographic difference.…”
Section: Discussioncontrasting
confidence: 75%
“…This result is higher than the SSC prevalence of previous studies in Tanzania and Ethiopia. Less than 1% of Tanzanian women reported early SSC [ 22 ], and the proportion of women in Ethiopia who had early SSC after childbirth was 9.2% and 28.1% [ 26 , 31 ]. However, the finding was low as compared to studies in high-income countries in which SSC practice rate was up to 99.0% [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Independent variables: household wealth quintile: poorest, poorer, middle, richer, and richest, was computed by MICS in a conventional approach from population-based data using a set of household assets [ 29 , 30 ]; child sex: male vs. female; ethnicity: Mandinka, Wollof, Fula, Jola, Sarahule, other groups and non-Gambians; health insurance coverage: insured vs. not insured; educational level: pre-primary or none, primary, secondary+, functionality difficulty: has functional difficulty vs. has no functional difficulty; total children ever born: 1-2, 3-4, 5+; marital status: currently married/in union, formerly married/in union, never married/in union; residential status: urban vs. rural; age at first marriage/union: < 18 years, 18-20 years, 20+ years; estimation of overall happiness: very happy, somewhat happy, neither happy nor unhappy, somewhat unhappy, very unhappy; duration in residence: internal immigrant (lived in community < 5 years) vs. native (lived in community for 5+ years); maternal age (years): 15-19, 20-24, 25-29, 30-34, 35-39, 40-44, 45-49; frequency of listening to radio or watching TV: not at all, less than once a week, at least once a week, almost every day; received ANC: yes vs. no; ANC visit initiation: early booking (within 1st trimester) vs. late booking (after 1st trimester); place of delivery: home vs. health facility; birth weight: low birthweight (< 2.5 kg) vs. normal weight (at least 2.5 kg); local government area: Banjul, Kanifing, Brikama, Mansakonko, Kerewan, Kuntaur, Janjanbureh, Basse. Some of these were selected as used by previous authors [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…Yılmaz-Esencan ve arkadaşlarının (2018), özel ve devlet hastanesinde gebe eğitim okuluna katılmış ve eğitim almış gebelerin doğum şekli, ilk emzirme zamanı ve TTT uygulamalarını değerlendirdikleri çalışmalarında kadınların %53.3'ünde TTT'nin sağlanmadığı saptanmıştır 15 . Etiyopya da yürütülen araştırmada da postpartum dönemde ten temasının uygulanma oranı %28.1 olarak belirtilmiştir 17 . Annelerin sürece hazır olmaması, uygulama konusundaki bilgi yetersizliği TTT'nin gerçekleştirilmesini engelleyebilmektedir.…”
Section: Discussionunclassified
“…Araştırmada primipar gebelerin TTT uygulamasının gerçekleştirilmesinde anlamlı düzeyde başarılı oldukları saptanmıştır. Ancak Bedaso ve arkadaşlarının yapmış olduğu araştırmada paritenin TTT uygulamasının gerçekleştirilmesinde bir etkisinin olmadığı belirtilmiştir 17 . Bu durum kadınların kişisel özelliklerine göre değişiklik gösterebilmektedir.…”
Section: Discussionunclassified